PENGARUH LATIHAN DRIBBLE MENGGUNAKAN SATU KAKI DOMINAN DAN DUA KAKI BERGANTIAN (Universitas Negeri Semarang, 2016)
Research methods with experimental M-S patterns or macthing by subject design. This research population is 14 years old students of SSB Tunas Muda Ngroto in 2015, the sample number is 20 people with purposive sample technique. The research variables consist two independent variables, namely one dominant leg dribble and two legs alternately dribble, then the dependent variable is the speed of ball dribbling. The instrument of tests uses dribbling speed test. Statistical data analysis uses t-test with significance level is 5% and db = n-1. The results of data analysis use significance level 5% can be concluded that: (1) There is an effect of the exercise for one dominant leg dribble to the speed of dribbling in the football game, because tcount (4.518)> ttable (2.262). (2) There is an effect of exercise using two legs alternately dribble to the speed of dribbling on the football game, because tcount (10.333)> ttable (2.262). (3) No influence of the exercise on one dominant leg dribble and two legs alternately dribble to the speed of ball dribbling, because tcount (1.550) <ttable (2.262). However, the average results of dribbling exercise with two legs (72.958) showed better results than one leg (67.221).